2018
DOI: 10.29259/sijdeb.v2i2.123-138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Online Behavioral Advertising Implementation on Attitude Toward Ad and Purchase Intention in Indonesian E-Marketplace

Abstract: Internet user increase certainly support e-commerce growth. So some e-commerce companies perform online behavioral advertising (OBA) to get consumers as much as possible. The current study uses retargeted ads as a kind of the latest OBA which most of e-marketplaces in Indonesia implement the ads. Survey in the form of questionnaire from 261 respondents. The respondents were showed by author the example of e-marketplace’s online behavioral advertising picture and video first before answering the questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
4
1
1
Order By: Relevance
“…It is revealed that online behavioral advertising is a key determinant of intention to purchase; this is compatible with previous literature Barnard (2014), Kusumawati (2017) and Rony (2018). On the contrary, the negative effect of online behavioral adverting on perceived risk is not significant and it contradicts with previous studies Barnard ( 2014) Kusumawati (2017) and Fachryto and Achyar (2018). This would need a further research and other studies to examine this kind of linkage.…”
Section: Conclusion and Discussioncontrasting
confidence: 61%
“…It is revealed that online behavioral advertising is a key determinant of intention to purchase; this is compatible with previous literature Barnard (2014), Kusumawati (2017) and Rony (2018). On the contrary, the negative effect of online behavioral adverting on perceived risk is not significant and it contradicts with previous studies Barnard ( 2014) Kusumawati (2017) and Fachryto and Achyar (2018). This would need a further research and other studies to examine this kind of linkage.…”
Section: Conclusion and Discussioncontrasting
confidence: 61%
“…Thus, consumers feel that their privacy has been known, followed, observed, and tracked. From previous studies, when marketers create messages that use consumer information that is too personal, it can significantly bring out a sense of creepiness that is felt by consumers (Barnard, 2014;Fachryto and Achyar 2018). A hypothesis is formulated which predicts that the personalization that a person feels from social media advertising will positively affect a sense of creepiness.…”
Section: Perceived Ad Personalizationmentioning
confidence: 99%
“…Namun demikian, sinergi yang dilakukan tetap harus diupayakan agar tidak sampai membuat masyarakat merasa terganggu akibat intensitas iklan yang terlalu tinggi. Iklan yang disampaikan secara berlebih dengan memanfaatkan banyak media massa justru dapat ditafsirkan oleh masyarakat sebagai iklan yang manipulatif, yang dapat mendorong terciptanya respon negatif (Fachryto & Achyar, 2018).…”
Section: Tinjauan Literatur Iklan Sebagai Media Komunikasiunclassified